Ambitious, misaligned, or uncertain? The occupational and educational aspirations of immigrant-origin youth in Germany - Alessandro Ferrara; Zerrin Salikutluk (Journal of Ethnic and Migration Studies, 2024)
Immigrant-origin students often hold higher educational aspirations than native-origin peers, accounting for socioeconomic status and school grades. The consequences of this `Immigrant Aspiration Paradox' (IAP) on their socioeconomic attainment are debated. Although individuals' occupational aspirations and how they compare with their educational aspirations (i.e. their alignment) also affect status attainment, they are understudied in the IAP literature. We contribute to the debate on the benefits of the IAP by investigating immigrant-native gaps in the level, (mis)alignment, and (un)certainty of teenage occupational and educational aspirations and their consequences on educational attainment in Germany. First, we describe immigrant-native gaps in teenage aspirations. Then, we investigate whether these differences mediate immigrant-native gaps in upper secondary attainment and tertiary enrollment. In line with the immigrant optimism theory, Asian-origin and Turkish-origin students are more likely to hold aligned high aspirations. On average, immigrant-origin students are less likely to have aligned low aspirations compared to native-origin students, and equally likely to hold misaligned or uncertain aspirations. We find that students from most immigrant-origin groups have a higher upper secondary attainment and tertiary enrollment than native-origin students, net of controls. Large portions of these advantages are mediated by the aspirations of immigrant-origin students, which we interpret as evidence of the benefits of the IAP.
Keywords: 320; Immigrant aspiration paradox; occupational aspirations; educational aspirations; aspiration alignment; immigrant optimism